Legal Construction of Asset Recovery for Crime of Corruption in Indonesia - Cahyani, Tinuk Dwi; Salmah, Halimatus Khalidawati (KnE Social Sciences, 2024)
Indonesia has made efforts to prevent and eradicate criminal acts. However, the reality is that corruption is still a problem in Indonesia. Corruption occurs in various aspects of state life and institutions, not only central government institutions but also regional governments. Corruption has bad impacts ranging from lowering the level of people’s welfare, destroying morality, and the foundations of national resilience. As time goes by, acts of corruption are carried out in various ways and are increasingly organized. More strategic efforts are needed to deal with this because corruption does not only talk about criminal acts and the perpetrators but is also related to the results of that corruption. The first question is how is corruption in Indonesia today? Second, what is the proper legal reconstruction to deal with it? Then to answer these problems, this research was made using an analytical descriptive method and a normative juridical approach by adding a set of data, one of which was from the n Vivo application. According to this study, there is still a lot of corruption in Indonesia, and because the state must also receive the benefits of criminal acts of corruption, there is a need for special rules that can carefully monitor in order to carry out asset recovery. Keywords: construction, corruption asset recovery